Pathogens and Immigrants: A Critical Appraisal of the Behavioral Immune System as an Explanation of Prejudice Against Ethnic Outgroups - Kusche, Isabel; Barker, Jessica L. (Frontiers in Psychology, 2019)
The last two decades have seen the development of a body of literature in evolutionary psychology that seeks to attribute negative attitudes to ethnic and racial minorities and other outgroups to an evolved behavioral immune system (BIS). It hypothesizes that disgust sensitivity, which evolved as protection against pathogen threats, also triggers reactions to cues that are not viscerally disgusting, such as people with unfamiliar features, and thus can explain prejudice towards members of these groups. Such an explanation seems to limit the influence of education, public policy and rhetoric on those attitudes. Our conceptual analysis shows that this is not the case. Existing hypotheses about why the BIS would be triggered even in the absence of visceral disgust elicitors suggest that general unfamiliarity or atypicality act as cues for this hypersensitive threat detection system. This implies that the impact of the BIS must depend on the cultural and societal context in which people learn not only what is disgusting but also what is typical. The social context of personal interaction with, mass media representation of and political debate about immigrants consequently needs to be considered as a decisive factor for any effect of the BIS on attitudes and behavior towards ethnic and racial outgroups. The BIS is therefore not a separate or even superordinate explanation of prejudice, compared to those coming from the social sciences. We conclude that it can offer valuable insights into processes of stigmatization and prejudice, once the role of social learning in the developmental unfolding and activation of psychological mechanisms is taken seriously.